Lit! : a Christian guide to reading books - Reinke, Tony, 1977- (Wheaton, Ill. : Crossway, 2011)
I love to read. I hate to read. I don't have time to read. I only read Christian books. I'm not good at reading. There's too much to read. Chances are, you've thought or said one of these exact phrases before because reading is important and in many ways unavoidable. Learn how to better read, what to read, when to read, and why you should read with this helpful guide from accomplished reader Tony Reinke. Offered here is a theology for reading and practical suggestions for reading widely, reading well, and for making it all worthwhile. - Publisher.
Pt. 1. A theology of books and reading. Paper pulp and etched granite : laying the cornerstone of our theology of books -- Wide eyed into the Son : how personal sin and the Gospel shape our literacy -- Reading is believing : savoring books in an eye-candy culture -- Reading from across the canyon : how a biblical worldview equips us to benefit from books -- The Giver's voice : seven benefits of reading non-Christian books -- The God who slays dragons : the purifying power of Christian imagination -- pt. 2. Some practical advice on book reading. Read with resolve : six priorities that decide what books I read (and don't read) -- How to read a book : 20 tips and tricks for reading nonfiction books -- Literature is life : tapping into the benefits of fiction literature -- Too busy to read : six ways to find (and protect) the time you need to read books -- Driven to distraction : how Internet habits cripple book reading -- Marginalia : the fine art of defacing books with pencils, pens, and highlighters -- Reading together : building community one book at a time -- Raising readers : how parents and pastors can encourage a love of book reading -- Happily ever after : five marks of a healthy book reader.
Includes bibliographical references (p. 189-202).
Keywords: Christians -- Books and reading; Reading